English Teacher’s And Students Responses To Learning English Using Blended Learning At Senior Vocational School - Yuliasari, Ulfa; Panggabean, Christina Innocenti Tumiar; Kurniawati, Dyah; Wardhono, Agus (DIDAKTIKA, 2023)
Due to Covid-19, students are required to study online at home, and currently, in the New Normal Era, student learning at school is allowed to study face-to-face although they must remain careful. Learning in current conditions has changed, and teachers must be able to adapt and develop learning models which could make it less complicated for students to understand the material being taught. Therefore, the present Blended Learning learning model is one model to overcome this problem. The Blended Learning model is a learning process that utilizes various approaches, namely by utilizing various kinds of media and technology offline and online. This study aims to determine the response to the application, problems, and solutions using the Blended Learning model in English subjects, as well as the problems faced by the teacher and how to overcome the application of the model. The sample of this studies is 7 teachers who teach English subjects and have implemented the Blended Learning learning model and 45 students from various majors at SMKN 2 Tuban. This research is a type of qualitative descriptive research with data collection techniques using questionnaires and interviews.